Management and Administration of Monitoring and Supervision in Early Childhood Education - Ananda Zuhrotul Hanin; Lubna Maulydia; Mafazah Fithriyyah; Suhardi Suhardi (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study examines the role of management, administration, monitoring, and supervision in improving the quality of education in Early Childhood Education (PAUD). Through a literature study, it was found that the success of PAUD institutions depends on the synergy of these four aspects. Administration plays a role in planning, recording, and managing education systematically. Management emphasizes the management of human resources, infrastructure, and efficient learning program planning. Monitoring is responsible for ensuring that program implementation aligns with established quality standards. Supervision provides professional guidance to teachers through observation, training, work evaluation, and coaching. The main obstacles in the field include a lack of qualified educators, minimal continuous training, and limited facilities and budget. The proposed solutions include adding more educators, increasing routine training, utilizing technology in supervision, and strengthening collaboration among principals, supervisors, and the community. With consistent and integrated implementation, management and administrative monitoring and supervision in PAUD can create an adaptive, professional, participatory educational environment focused on continuous quality improvement.